Forced migration, gender, social capital and coping strategies in Western Tanzania. - Wambugu, Lydia W. (My University, 2011)
This exploratory qualitative research systematically analyses the coping experiences of a group of refugee women from Burundi, Rwanda and the Democratic Republic of the Congo (DRC), rsiding in the western Tanzanian region of Kigoma nd Kagera. The literature reviewed points out that whilest there are still many identified gaps and aspects yet to be documented, it is evident that refugee women are among the social groups most affected by the phenomenon of forced migration and displacement. The study explores the kind of coping strategies refugee women adopted under difficult circumstances, and how the women responded to experiences that they frequently described in terms of concrete and material realities...
Ph.D. - CLM
Keywords: Migration, Forced; Gender; Social capital; Tanzania